On some problems in describing ⁴He(e,e′) reaction - Kuplennikov, E.L.; Nemashkalo, A.A.; Ranyuk, Yu.N (Вопросы атомной науки и техники, 2004)
Inelastic ⁴He(e,e′) energy spectra and response functions together with realistic calculations are considered. It was found that at the threshold region models predict far less cross section and response functions strength than are experimentally observed.